Modernising European Legal Education (MELE) Innovative Strategies to Address Urgent Cross-Cutting Challenges - Gstrein, Oskar J.; Fröhlich, Mareike; van den Berg, Caspar; Giegerich, Thomas (European Union and its Neighbours in a Globalized World, 2023)
This open access book presents innovative strategies to address cross-cutting topics and foster transversal competences. The modernization of European legal education presents a compelling challenge that calls for enhanced interdisciplinary collaboration among academic disciplines and innovative teaching methods. The volume introduces venues towards education innovation and engages with complex and emerging topics such as datafication, climate change, gender, and the aftermath of the COVID-19 pandemic. The insights presented not only emphasize the importance of preserving traditional approaches to legal disciplines and passing them on to future generations, but also underscore the need to critically reassess and revolutionize existing structures. As our societies become more diverse and our understanding of legitimacy, justice, and values undergoes transformations, it is imperative to reconsider the role of traditional values while exploring promising alternative approaches.